BUNGA MELATI DALAM KARYA TAPESTRI - Drs. Mediagus, M.Pd.,, METRA OKTAVIA, Drs. Erwin A, M.Sn., (Jurusan Seni Rupa FBS UNP Padang, 2018)
This final work aims to create jasmine flower through tapestry withvarious compositions. Techniques used in making this final work is the techniquegiordes, soumak technique, and flat technique. This final process of creationmethod uses five stages : preparation stage, elaboration stage, synthesis stage,concept realization stage starting from sketching, preparing tools and materials,moving sketches, making process, and finishing. The final stage is the completion of the exhibition and cataloging of works and reports. The resulting tapestry of jasmine flower is titled respectively: Tranquility, Puspa Bangsa, Happiness, Decoration, Tenderness, Sadness, Purity. It is hoped that this final work can be useful for art and society department. As a material appreciation and comparative work to create a better tapestry work in the future.Keywords : Jasmine Flower, Tapestry